Genus Spondias: A Phytochemical and Pharmacological Review. (12th February 2018) - Sameh, Salma; Al-Sayed, Eman; Labib, Rola M.; Singab, Abdel Nasser
Abstract : It is believed that many degenerative diseases are due to oxidative stress. In view of the limited drugs available for treating degenerative diseases, natural products represent a promising therapeutic strategy in the search for new and effective candidates for treating degenerative diseases. This review focuses on the genus Spondias which is widely used in traditional medicine for the treatment of many diseases. Spondias is a genus of flowering plants belonging to the cashew family (Anacardiaceae). This genus comprises 18 species distributed across tropical regions in the world. A variety of bioactive phytochemical constituents were isolated from different plants belonging to the genus Spondias . Diverse pharmacological activities were reported for the genus Spondias including cytotoxic, antioxidant, ulcer protective, hepatoprotective, anti-inflammatory, antiarthritic, and antidementia effects. These attributes indicate their potential to treat various degenerative diseases. The aim of this review is to draw attention to the unexplored potential of phytochemicals obtained from Spondias species, thereby contributing to the development of new therapeutic alternatives that may improve the health of people suffering from degenerative diseases and other health problems.